Endocytosis and non-canonical autophagy mediate extracellular histones cytotoxicity in vascular models of sepsis - Garcés, C.; Tascón, P.; Diago-Domingo, Luis; Ibáñez, A. J.; Herrera, G.; Rodríguez, L. R.; Salewskij, K.; Jonsson, G.; Penninger, J. M.; Romá-Mateo, C.; Pallardó, F. V. (Frontiers in Immunology, 2026)
IntroductionSepsis, a widespread global ailment, involves an exaggerated immune response, leading to hyperinflammation and immunosuppression. Extracellular histones, released during hyperinflammation as part of the defensive response against pathogens, significantly contribute to sepsis pathogenesis, compromising viability of the host’s endothelial cells and contributing to organ failure.MethodsThis study explores the link between cytotoxic effects of extracellular histones and endocytosis mechanisms in human umbilical vein endothelial cells (HUVECs) and blood vessel organoids (BVOs) incubated with extracellular histones and different modulators of endocytosis mechanisms.ResultsExposure to various doses of purified extracellular histones in both HUVECs cultures and BVOs revealed sub-lethal doses leading to histone entry and colocalization with the autophagy mediator LC3B, whereas high doses induced cytotoxicity. Incubating cells or organoids at low temperature before histone exposure prevented entry, reducing colocalization with LC3B and cell death; moreover, inhibition of clathrin-mediated endocytosis abrogated histone entry into HUVECs and prevented their cytotoxic effects, whereas inhibition of caveolin-mediated mechanisms had no effect.DiscussionIn summary, this study offers insights into histones’ cytotoxicity and functional interactions with the LC3B-mediated, non-canonical autophagy pathway, enhancing our understanding of the molecular bases of sepsis pathophysiology within HUVEC and blood vessel organoids.